Predictors of radiographic progression for NTM–pulmonary disease diagnosed by bronchoscopy. (January 2020) - Huang, Hung-Ling; Lee, Meng-Rui; Liu, Chia-Jung; Cheng, Meng-Hsuan; Lu, Po-Liang; Wang, Jann-Yuan; Chong, Inn-Wen
Abstract: Objectives: A single isolate of nontuberculous mycobacterium (NTM) from bronchoscopic samples satisfies the microbiological criterion for diagnosing NTM-pulmonary disease (PD). Studies investigating patients with NTM-PD and multiple culture-negative sputum samples but culture-positive bronchoscopic samples are lacking. We investigated the clinical characteristics, outcome, and predictors of radiographic progression in this special population. Methods: Patients with negative NTM culture from ≥2 expectorated sputum samples within the 3 months prior to bronchoscopy diagnosis of NTM-PD between 2009 and 2017 were included. Patient characteristics and clinical course were described. Predictors for radiographic progression of NTM-PD within 2 years were analysed by using multivariate logistic regression. Results: Among 66 patients with bronchoscopy-diagnosed NTM-PD, radiographic progression occurred within 2 years in 17 (26%). Of the 60 patients not initially treated, radiographic progression occurred in 17 (28%). Among them, 10 never received treatment, with 6 deteriorating and 3 dying. Of the 6 and 7 patients who received treatment immediately after NTM-PD diagnosis and after radiographic progression, respectively, none had further radiographic progression. The independent predictors of radiographic progression were male sex, body mass index <18.5 kg/m 2, use of inhaled corticosteroids, and acid-fast smear grade ≥2 of index bronchoscopic samples. Conclusions: Among patients with bronchoscopy-diagnosed NTM-PD, one fourth experienced radiographic progression within 2 years. The risk was even higher in those with the aforementioned predictors, immediate treatment or close monitoring is recommended. For others, conservative management by regular microbiological monitoring for sputum samples and image follow-up may be the optimal choice. Highlights: Risk of radiographic progression in 2 years was 28% in bronchoscopy-diagnosed NTM-PD. Male sex, low BMI, ICS use and index sample AFS ≥2 + were poor prognostic factors. Half with ongoing radiographic progression died within 2 years if left untreated.